2020
DOI: 10.3390/s20082332
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Control of Unmanned Aerial Vehicle as Communication Relay to Optimize Ground-to-Air Uplinks

Abstract: In recent years, unmanned aerial vehicles (UAVs) have been considered an ideal relay platform for enhancing the communication between ground agents, because they fly at high altitudes and are easy to deploy with strong adaptabilities. Their maneuvering allows them to adjust their location to optimize the performance of links, which brings out the relay UAV autonomous mobility control problem. This work addressed the problem in a novel scene with mobile agents and completely unknown wireless channel properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The development of the general control law continues by computing ̄ ∈ ℝ similarly to (7), namely through…”
Section: Subsequently Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the general control law continues by computing ̄ ∈ ℝ similarly to (7), namely through…”
Section: Subsequently Settingmentioning
confidence: 99%
“…In addition, new research has shown that drones are able to effectively be employed as communication relays 5,6 between ground units, allowing them to overcome communication difficulties caused by obstacles or terrain features, such as buildings or mountainous terrain. The approach in these works often assumes a centralized level of coordination 7 , known locations of ground units 8,9 , or focuses on a small finite subset of connectivity topologies within decentralized frameworks 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they did not study dense urban areas. Wu et al 37 studies UAV mobility control issues as a communication relay on multiagents' on-demand service. It takes mobile agents and entirely unknown wireless channel properties, using only online measured data on collected agent location information and received signal strength (RSS).…”
Section: Cellular-to-uav Path Loss For Uavmentioning
confidence: 99%
“…The smart service-centric domain includes aerial delivery [3], smart healthcare, smart homes, Internet of vehicles [4], UAV simulation [5], pollution monitoring, smart agriculture, disaster management [6], industrial Internet of Things, and green mobility [7]. It has emerged as a prominent development area to revolutionize UAV-assisted IoT in daily day life [8]. In sensor-enabled UAV-assisted applications, for transmitting and viewing data immediately, the Internet is utilized to connect actuators and sensors inside the aerial vehicles.…”
Section: Introductionmentioning
confidence: 99%